Search for the meaning of life - Ramakrishnan, Prabha (Universiti Teknologi MARA, Sarawak, 2004)
The article "Search For The Meaning Of Life" by Prabha Ramakrishnan describes the writer's reflection on the meaning of life after reaching the age of fifty. The writer asks friends and searches the internet for answers but receives different views and no definite explanation. The article concludes that the meaning of life may be found through values such as kindness, beauty, and truth, inspired by the thoughts of Albert Einstein.